Predicting atelectasis by assessment of collateral ventilation prior to endobronchial lung volume reduction: a feasibility study - Gompelmann, Daniela; Eberhardt, Ralf; Michaud, G.; Ernst, A.; Herth, Felix (Respiration, 2010)
Background: The advent of endoscopic lung volume reduction (ELVR), especially relying on valve technology to achieve atelectasis, has aroused new interest in the assessment of collateral ventilation, which has been implicated in ELVR failures. We are reporting on the use of a catheter-based device that measures airway pressures and flows, and calculates airway resistance in vivo. Objectives: To assess the safety of this catheter-based system and the feasibility of obtaining measurements predictive of atelectasis after ELVR. Methods: Patients undergoing ELVR were prospectively included in this double-blind cohort study. Each lobe targeted for ELVR was blocked with a catheter system (Chartis® System; Pulmonx, Inc., Redwood, Calif., USA); pressures and flows were assessed continuously. The primary endpoints were to evaluate the safety and feasibility; the secondary endpoint was to assess whether there was a relationship between the measurements and the incidence of atelectasis following ELVR. Results: From June 2008 to November 2008, 25 patients were included in the study. All procedures could be performed without any complications. Due to pneumothorax in 1 case and inability to assess the catheter-based measurements in 4 cases, the final analysis included 20 patients. Atelectasis occurred in 8 out of 20 cases following implantation. In 18 patients (90%), the resistance measurements correlated with the postimplantation atelectasis visualized on a chest X-ray; in 2 patients (10%), a mismatch was detected. Conclusions: Resistance measurements were safely and successfully achieved. In 90% of the analyzable cases, the resistance measurements correlated with the occurrence of atelectasis after ELVR. The clinical impact of these findings will need to be evaluated in subsequent trials.